Structural, magnetic and electrical properties of La-A-Mn-O (A=Ca, Sr, Ba, Na and K) in bulk and thin film - Ng, Siau Wei (2011)
Perovskite manganites oxide materials have attracted much attention due to their promising potential applications in the magnetic sensor or devices. In this research, La1-xAxMnO3 (x = 0.33 when A=Ca, Sr and Ba; x= 0.2 when A=Na and K) in bulk form were prepared via solid state reaction method. La0.67Sr0.33MnO3 (LSMO) and La0.8Na0.2MnO3 (LNMO) are then converted to thin film via pulse laser deposition method (PLD) on different substrates (corning glass, fused silica glass and MgO (100)) and deposition duration. Rietveld refinement of X-ray diffraction data showed that all samples are polycrystalline having trigonal crystal structure except for La0.67Ca0.33MnO3 (LCMO) and La0.67Ba0.33MnO3 (LBMO) which are orthorhombic. From the Rietveld refinement, we observed that the lattice parameter, Mn-O bond length and bond angle changed in thin film which were influenced by the substrates type and deposition duration. The thickness of films was in the range of ~0.3-3.0 μm. The crystallite size for the thin film is between 15-22 nm. The grain size distribution for bulk samples are around 1.0-2.0 μm. A huge change of surface microstructure can be observed for thin film samples, where the grain size is reduced to ~50-150 nm. Some nano-crack effects were observed in the thin film samples where this effect is due to the different coefficient of thermal expansion between the film and substrates during the annealing process. Thin film samples showed a much higher resistance (about 2-3 orders) due to the existence of disordered phase at the grain boundary and/or nano-crack barrier that causes higher scattering and/or tunneling effect when the electrons pass through them. The metal-insulator temperature (Tp) for LSMO shifted to lower values in the thin films, probably due to the change of Mn-O bond length and bond angle. Conversely, LNMO system showed greater Tp value in thin film suggesting that the grain boundary effect might also contribute to the Tp changes. Nonetheless, the deposition duration and substrates used also influence the Tp value. Overall, negative magnetoresistance (MR) have been obtained for bulk and thin films. The MR value increases with decreasing temperature at low applied magnetic field which known as Low Field Magnetoresistance (LFMR). In thin film form the %MR value has been improved with -25% for LS_M15 and -22% for LN_M20 as compared to that of the bulk LSMO (-16%) and LNMO (-21%) when a magnetic field of 1 Tesla was applied at 90 K.